(untitled) (Research, Society and Development, 2021)
This study aimed to analyze two cases of fracture of the metal framework of Co-Cr-based removable partial dentures, using fractography to identify a true cause of these failures. The first case concerned the coupling between the smaller and larger connectors; the patient brought his fractured removable partial dentures to the clinic. The second case referred to a larger connector; structure of the patient fractured during the test. For failure analysis, images of two fractured metal frameworks were taken by scanning electron microscopy to identify the origin of the fracture and to determine the mechanisms involved in the process. Subsequently, energy dispersive X-ray spectroscopy was used for elemental chemical mapping of the fracture interface. The fractography indicated material fatigue as a possible cause in the first case and an error in the casting process in the second. The energy dispersive X-ray spectroscopy test, performed in the specimen of case B, showed predominant and characteristic peaks for Co and Cr, with a higher concentration of chromium. The fractures identified were associated with inclusions and with material fatigue and a number important characteristics were evidenced by the technique.